(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
In the digital age, the integration of modern pedagogical technologies has transformed language education, offering innovative tools and resources to enhance teaching and learning experiences. This article explores the role of modern pedagogical technologies in teaching foreign languages, examining the benefits of technology-enhanced language instruction, exploring emerging trends in digital language learning, and discussing practical strategies for integrating technology into language teaching practices. By harnessing the potential of modern pedagogical technologies, educators can create dynamic and interactive language learning environments that foster engagement, collaboration, and proficiency